Perceptions of pre university (form six) students toward career in entrepreneurship - Loleh, bin Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2014)
This is a research study that examines form sixth students perception about a career in the field of entrepreneurship in Sri Aman, Sarawak. It aims to identify the perceptions of students, student interest and resources affecting students about entrepreneurship among students in the sixth form. This study is a descriptive and inferential study. A total of 112 students were selected randomly. All information was obtained using a questionnaire and interviews. The analysis was done using SPSS 21.0 for Windows software. The study found that no demographic factors influencing students' perceptions of entrepreneurship as a career. In addition, there is a positive and significant relationship between student perception and student interest in entrepreneurship. Furtermore, a positive and significant relationship also found in student perception and source of encouragement about entrepreneurship. Result also show the positive and significant relationship between student perception and influences of entrepreneurhip program. It is hoped that this study would provide benefits to certain parties, especially the management of the school to serve as a guideline for improving mnat students to entrepreneurship as a career. Other than that hopefully this study can serve as a guide to researchers conducting similar studies in the future.